ANALISIS TINGKAT KESUKAAN SNACK BAR DENGAN PENAMBAHAN TEPUNG CANGKANG RAJUNGAN - Nur Latifah, Atik; Rochima, Emma; Pratama, Rusky Intan; Rostini, Iis (Universitas Mataram, 2025)
Blue Swimming Crab (Portunus pelagicus) has a calcium content in the crab shell of 19.97%, which has the potential to be used as an additional ingredient in snack bar products. This study aims to determine the concentration of blue swimming crab shell flour to produce the snack bars that panelists prefer. The study was conducted from October to December 2024 at the Fisheries Product Processing Laboratory, Faculty of Fisheries and Marine Sciences, Padjadjaran University, Nutrition Laboratory, Faculty of Animal Husbandry, Padjadjaran University, and Saraswati Indo Genetech Laboratory, Bogor. The research is classified as experimental research with a Completely Randomized Design method, namely making snack bars with the addition of crab shell flour with four treatments (0%, 1.5%, 2.5%, and 3.5%) and 25 semi-trained panelists as replications to determine the level of panelist preference for snack bars. Data analysis was done using the Friedman and Bayes tests to determine the best treatment. The parameters observed were the organoleptic and chemical content of the snack bar. The results showed that the most preferred addition of crab shell flour was the 2.5% treatment because it had the most significant alternative value of 8.61 with an average appearance of 8.0, aroma of 8.3, texture of 7.4, and taste of 7.9. The chemical characteristics produced by this treatment: 1.75% water content, 2.85% ash content, 9.62% protein content, 12.93% fat content, 72.85% carbohydrate content, and 436.48 mg/100 g calcium content